Perencanaan Instalasi Pengolah Lumpur Tinja Sistem Kolam Kota Palembang (Studi Kasus: IPLT Sukawinatan) - Dwi Oktarina; Helmi Haki (Jurnal Teknik Sipil dan Lingkungan, 2013)
Faecal sludge  treatment installation is designed to receive and treat faecal sludge which is collected from citizen. This facility is one of efforts that we can use to improve  the quality  of   wastewater treatment especially in faecal sludge treatment.Palembang city has its own faecal sludge treatment installation facility which is located at Kecamatan Sukarame, Kelurahan Sukajaya. The total area of  facility is about 6 Ha. This facility has only six sedimentation pond.Within years pass by, the increase of  citizen amount makes the volume of  faecal sludge which is produced by citizen increasing and it’s exceed the earlier designed volume. Therefore, we need to recalculating the volume of faecal sludge. So then, they could be accomodated by Faecal Sludge Treatment Installation  Sukawinatan.The purpose of this research are calculating the volume of faecal sludge which produced by Palembang citizen, calculating the average of input faecal sludge, and calculating the percentage of faecal sludge which got into Faecal Sludge Treatment Installation. Discovering the condition of installation facility and designing a proper faecal sludge treatment installation with pond system.As the results of this research are that there’s  still a lack of  awareness to deplete the existing of faecal sludge which deposits in the septic tank owned by each of Palembang’s residents. The proper and suitable design (PU Departement standard) of faecal sludge treatment with pond system. Keywords: faecal sludge, sedimentation pond, volume of faecal sludge, installation designed